An analysis of the challenges faced by youth in accessing the Zimbabwe youth empowerment fund: the case of Mutare district - Mateta, Patience (Midlands State University, 2018)
The research aimed at analysing the challenges faced by youth in accessing the youth fund using Mutare District as the case study. The researcher went further to illustrate various legal frameworks that the government has established in a bid to deal with the economic, social and political problems facing youth in Zimbabwe. The researcher has focused on the duty of the government in ensuring the fulfillment of the needs of the youth in Zimbabwe. The study looked at the importance of youth empowerment in the form of youth fund whereby the government of Zimbabwe has launched various Youth Fund schemes aimed at curbing unemployment in the country. This study had focused on the Kurera/Ukondla Youth Fund which was launched by the government to enable youth to start their own businesses so that they can support themselves. The researcher also looked at the causes and effects of unemployment and other countries that have been involved in the empowerment programmes. The study findings have shown that the challenges faced by youth in acquiring funds are mainly caused by the funding institutions themselves for example the politicization and corruption on the distribution of these funds has been a major challenge faced by Youth in Mutare District. The researcher has recommended on what the government should do in order to solve the problems that the youth are facing in accessing funds thereby ensuring a successful youth empowerment in the country.